Socially Responsible Investment, Microfinance and Banking: Creating Value by Synergy. Issue 1 (June 2018) - Praseeda, Challapalli
Abstract: Socially responsible investing (SRI) is fast catching the imagination of the ever increasing social consciousness of the investor community. Emergence of SRI can be traced back to the 1970s to few socially conscious investors who wanted to invest in bonds other than war, arms and ammunition and alcohol. Traditionally, SRI has focused on the economic social and governance (ESG) areas.Dieckmann (2007) who authored; Microfinance an emerging investment opportunity as a part of the Deutsche Bank Research, indicates that the SRI sector is witnessing the emergence of novae entrants like the microfinance (MF). The report also states that MF is scanning the environment for new funding opportunities by securitising MF opportunities and moving to the extent of going public. The scenario suggests microfinance to be robust, low risk profiled and growing investment avenue, which is fast emerging in the field of SRI. The purpose of the present article is to explore into the different dimensions of this emerging phenomenon and understand the emerging opportunities for banks in creating value using the synergy of SRI and MF.